Supervisor Bottom-Line Mentality as a Precursor to Employee Incivility: The Depleting Role of Self-Regulation and the Buffering Influence of Trait Mindfulness a Mediated Moderation Mechanism (Journal of Asian Development Studies, 2026)
This study investigates how supervisor bottom-line mentality (SBLM) drives employee incivility in FMCG B2B organizations, based on Conservation of Resources (COR) theory. It examines self-regulation depletion as a mediator and trait mindfulness as a moderator. The study surveyed full-time employees in several FMCG B2B firms and analyzed the data using SPSS 27. Results show SBLM directly increases incivility, with self-regulation depletion mediating this effect. Trait mindfulness buffers the damaging impact of SBLM. These findings underscore the need to reconsider supervisory practices that prioritize bottom-line results at the expense of employee well-being. Mindfulness interventions reduce these negative effects and help build a healthier workplace. This research clarifies the psychological mechanisms linking bottom-line mentality to incivility and shows the protective role of mindfulness.